2019
DOI: 10.1017/s0149767719000305
|View full text |Cite
|
Sign up to set email alerts
|

A Dance of Resistance from Recife, Brazil: Carnivalesque Improvisation in Frevo

Abstract: Frevo is an energetic dance from Recife, the capital of Brazil's northeastern state of Pernambuco. Frevo is a dance of resistance because it narrates complex notions of identity that contribute to social empowerment through strategic processes of liberation for marginalized groups. The dance originates from the Brazilian martial art of capoeira and it is carnivalesque because it is performed in crowded, often violent streets during carnival, when power hierarchies are disrupted. Through this ethnographic resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Dance, for its performative nature, is a "seductive way of embodying national or regional identities" (Neveu Kringelbach 2013, 10). Many dance studies have revealed that, when dance concerns one's or others' identities, it is a particularly salient vehicle to politically demonstrate such identities (Neveu Kringelbach and Skinner 2012;Royce 2002;Wulff 2008;Weir 2017;Spanos 2019). North American native communities, for instance, revive the traditional dance rituals to mark their distinct identities (Aplin 2009;Kelley 2012) or to protest for political rights (Harkin 1997;Weir 2017).…”
Section: Cultural Renaissance and The New Generation Of Kahiko Dancersmentioning
confidence: 99%
“…Dance, for its performative nature, is a "seductive way of embodying national or regional identities" (Neveu Kringelbach 2013, 10). Many dance studies have revealed that, when dance concerns one's or others' identities, it is a particularly salient vehicle to politically demonstrate such identities (Neveu Kringelbach and Skinner 2012;Royce 2002;Wulff 2008;Weir 2017;Spanos 2019). North American native communities, for instance, revive the traditional dance rituals to mark their distinct identities (Aplin 2009;Kelley 2012) or to protest for political rights (Harkin 1997;Weir 2017).…”
Section: Cultural Renaissance and The New Generation Of Kahiko Dancersmentioning
confidence: 99%
“…The city is characterized by deep social inequalities: while it has the 13 th GDP of Brazil (Borba, 2022), more than 50% of its population is considered low-income (Santana, Medeiros, & Monken, 2022). On the other side, Recife is a cradle of a popular culture of nationally established rhythms, such as Frevo (Spanos, 2019) and Manguebeat (Mendonça, 2019). Most music videos belonging to this genre, which derive from the outskirts of the aforementioned city, present favelas both in their settings and lyrics (Bento, 2021a;Gericó, Souza, & Pereira, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A cidade é caracterizada por profundas desigualdades sociais: embora tenha o 13º PIB do Brasil (Borba, 2022), mais de 50% de sua população é considerada de baixa renda (Santana et al, 2022). Do outro lado, Recife é berço de uma cultura popular de ritmos consagrados nacionalmente, como o Frevo (Spanos, 2019) e o Manguebeat (Mendonça, 2019). A maioria dos videoclipes desse gênero, oriundos da periferia da referida cidade, apresenta favelas tanto em seus cenários quanto em suas letras (Bento, 2021a;Gericó et al, 2020).…”
unclassified